2007
DOI: 10.1111/j.1439-0418.2007.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of predatory ants on two lepidopteran insect pests in Indian cauliflower agroecosystems

Abstract: The impact of predatory, agroecosystem-nesting ant species on the larval stages of the two major lepidopteran pests, the diamondback moth (DBM), Plutella xylostella and the black cutworm (BC), Agrotis ipsilon, in cauliflower agroecosystem in Uttar Pradesh, India, was investigated in farmersÕ fields. Field observations revealed that six ant species, the most important being Pheidole sp., preyed on the crop-damaging stages of DBM and BC. Bait experiments with larvae of DBM and BC, placed randomly on the ground, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…1). Variance of these pests from season to season and region to region is comparable with the findings of Sachan and Srivastava, (1972), Sachan and Gangwar (1990) and Chaudhuri et al, (2001), Sarfarazet al, (2005 (Firakeet al, 2012, Jalali et al, 2003, Agarwal et al, 2007, Sood, 2004 Fig. 2).…”
Section: Resultssupporting
confidence: 79%
“…1). Variance of these pests from season to season and region to region is comparable with the findings of Sachan and Srivastava, (1972), Sachan and Gangwar (1990) and Chaudhuri et al, (2001), Sarfarazet al, (2005 (Firakeet al, 2012, Jalali et al, 2003, Agarwal et al, 2007, Sood, 2004 Fig. 2).…”
Section: Resultssupporting
confidence: 79%
“…The enriched material used as an organic amendment to paddy and tomato plants results in fertilizer responses in these plants and concomitant correlations between performance parameters and soil fertility attributes, in a dose-dependent manner. Since P. latinoda foragers also prey on economically important insect pests such as Plutella xylostella and Agrotis ipsilon (Agarwal et al, 2007), this ant species has the potential to improve crop plant fitness through multiple pathways. Thus, agroecosystem productivity can be enhanced by conserving and/or augmenting the colonies of P. latinoda.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we have reported that P. latinoda foragers prey on economically important insect pests such as Plutella xylostella and Agrotis ipsilon, in annual cropping systems (Agarwal et al, 2007). We have also found that the worker ants discard arthropod exoskeletons, seed fragments, leaves etc.…”
Section: Tablementioning
confidence: 93%
See 1 more Smart Citation
“…In addition to their role as bioindicators of environmental change, most ant species are efficient predators of other insects, contributing to pest control in crops (Perfecto, 1991;Agarwal et al, 2007;Rico-Gray & Oliveira, 2007;Lange et al, 2008). According to Booij and Noorlander (1992), ants, beetles and spiders are the most effective generalist predators in agrosystems.…”
mentioning
confidence: 99%